Policy-Oriented Research Impact Assessment (PORIA) case study on the International Food Policy Research Institute (IFPRI) and the Mexican PROGRESA: Anti-poverty and human resource investment conditional cash transfer program - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
In August 1997 Mexico introduced an innovative antipoverty program called PROGRESA (later called Oportunidades). PROGRESA/Oportunidades seeks to enhance the human resources of younger Mexicans by providing conditional cash transfers (CCTs) rather than particular foods (like milk and tortillas). It works to assure participation and some degree of empowerment of the more vulnerable members of poor households (women, infants, children) and makes systematic efforts at evaluation. The CCTs are made to the mothers in the household, on the condition that children and adolescents attend school, infants receive micronutrient supplements, mothers attend sessions on nutrition and health practices, and all family members have regular health and nutrition checkups. PROGRESA contracted with IFPRI to undertake an initial evaluation of PROGRESA in 1998-2000.